Laser Irradiation on Growth of Trichophyton Rubrum: An in Vitro Study - Ghavam, Seyed Alireza; Aref, Saeed; Mohajerani, Ezedin; Shidfar, Mohammad Reza; Moravvej, Hamideh (Journal of Lasers in Medical Sciences, 2014)
Introduction: Trichophyton rubrum is one of the most common species of dermatophytes which affects superficial keratinous tissue. It is not especially virulent but it can be responsible for considerable morbidity. Although there are different therapeutic modalities to treat fungal infections, clinicians are searching for alternative treatment because of the various side effects of the present therapeutic methods. As a new procedure, Laser therapy has brought on many advantages in clinical management of dermatophytes. Possible inhibitory potential of laser irradiation on fungal colonies was investigated invitro in this study. Methods: A total of 240 fungal plates of standard size of trichophyton rubrum colonies that had been cultured from the lesions of different patients at the mycology laboratory, were selected. Each fungal plate was assigned as control or experimental group. Experimental plates were irradiated by a laser system (low power laser or different wavelength of high power laser). The effects of different laser wavelengths and energies on isolated colonies were assessed. After laser irradiation, final size of colonies was measured on the first, the 7th and the 14th day after laser irradiation. Results: Although low power laser irradiation did not have any inhibitory effect on fungal growth, the Q-Switched Neodymium-Doped Yttrium Aluminium Garnet (Nd:YAG) laser 532nm at 8j/cm2, Q-Switched Nd:YAG laser 1064nm at 4j/cm2 to 8j/cm2 and Pulsed dye laser 595nm at 8j/cm2 to 14j/cm2 significantly inhibited growth of trichophyton rubrum in vitro. Conclusion: Q-Switched Nd:YAG 532nm at 8j/cm2, Q-Switched Nd:YAG laser 1064nm at 4j/cm2 to 8j/cm2 and pulsed dye laser (PDL) 595nm at 8j/cm2 to 14j/cm2 can be effective to suppress trichophyton rubrum growth.